Carbon Monoxide-Reacting Pigment from Desulfotomaculum nigrificans and Its Possible Relevance to Sulfite Reduction - Trudinger, P. A. (1970)
The separation of an autoxidizable brown pigment, P582, from Desulfotomaculum nigrificans is described. It reacted with Na(2)S(2)O(4) and was characterized by absorption maxima in the oxidized state at 392, 582, and 700 nm. In the presence of Na(2)S(2)O(4), P582 formed complexes with CO and, under alkaline conditions, pyridine. There was no reaction with cyanide. The molecular weight of P582 was approximately 145,000, and the purest preparations contained Fe, Zn, and acid-labile sulfide but not Cu, Mo, or Mn. Preparations of P582 catalyzed the reduced methyl viologen (MVH)-linked reduction of sulfite, hydroxylamine, and nitrite but not of sulfate, thiosulfate, or nitrate. Reduced pyridine nucleotides did not substitute for MVH. A major product of the MVH-sulfite reaction was sulfide. CO partially inhibited the enzymatic activities. Sulfite, hydroxylamine, and nitrite and CO caused changes in the spectrum of Na(2)S(2)O(4)-reduced P582. Fe(2+)-chelating reagents reacted with part of the Fe of P582 and caused partial losses of labile sulfide and enzymatic activity. The spectral and CO-reacting properties of P582 were, however, unaffected by chelating agents. The reaction between P582 and chelating agents was stimulated by reducing agents.